2010
DOI: 10.1038/bmt.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell as salvage treatment for refractory chronic GVHD

Abstract: Refractory chronic GVHD (cGVHD) is an important complication after allogeneic hematopoietic SCT and is prognostic of poor outcome. MSCs are involved in tissue repair and modulating immune responses in vitro and in vivo. From April 2005 to October 2008, 19 patients with refractory cGVHD were treated with MSCs derived from the BM of volunteers. The median dose of MSCs was 0.6 × 106 cells per kg body weight. Fourteen of 19 patients (73.7%) responded well to MSCs, achieving a CR (n=4) or a PR (n=10). The immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(149 citation statements)
references
References 40 publications
2
139
0
8
Order By: Relevance
“…These cells are clinically attractive, as they show very low immunogenicity, and they can induce immunosuppression in vitro and in vivo [15], and available data from clinical trials indicate that they are safe and have shown some efficacy in ameliorating GvHD and autoimmune disease outcome in patients [2,[4][5][6][26][27][28][29][30]. However, their mechanism of action is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells are clinically attractive, as they show very low immunogenicity, and they can induce immunosuppression in vitro and in vivo [15], and available data from clinical trials indicate that they are safe and have shown some efficacy in ameliorating GvHD and autoimmune disease outcome in patients [2,[4][5][6][26][27][28][29][30]. However, their mechanism of action is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of action of MSCs is not well understood, they have already entered into clinical trials and, given their low immunogenicity, few if any adverse events have emerged to date [2][3][4][5][6].…”
mentioning
confidence: 99%
“…In the first patient treated, we saw a partial response. 9 The largest study was from Weng et al 94 who reported on 19 patients with refractory chronic GVHD. These patients were treated with 1-5 doses.…”
Section: Stromal Cells For Treatment Of Chronic Gvhdmentioning
confidence: 99%
“…MSCs are often used for treating graft-versus-host disease (GVHD) (Weng et al, 2010;Le Blanc et al, 2008), suggesting that an infusion of MSCs may be an effective therapy for patients with steroid-resistant acute GVHD. The necdin homologue (mouse) (NDN), EPH receptor A5 (EPHA5), nephroblastoma overexpressed gene (NOV) and runt-related transcription factor 2 (RUNX2) are possible markers to describe culture status, including growth capacity and differentiation (Tanabe et al, 2008).…”
Section: Genes Representing the Mesenchymal Stem Cell Culture Stagementioning
confidence: 99%